Analysis of Customer Preferences and Willingness to Pay for Healthy Salad in Malang, Indonesia - Purba, Pebli Adenesli; Asmara, Rosihan; Andriani, Dwi Retno (Agro Bali : Agricultural Journal, 2025)
The growing trend of healthier eating habits, driven by increasing health awareness, presents a business opportunity for SMEs in the healthy food sector. This study investigates consumer preferences, attribute importance, and willingness to pay for vegetable salads in Malang, using a discrete choice experiment with a conditional logit model. A survey of 150 respondents who had purchased and consumed vegetable salads was conducted, analyzing key attributes, including health, mood, convenience, sensory appeal, natural content, and price, adapted from the food choice questionnaire and processed using R-Studio software. The findings indicate that consumers prefer vegetable salads that are high in fiber, free of additives, available in nearby shops, relaxing when consumed, and have a good taste. The ranking of attributes is important in purchasing decisions, as it follows the order of health, natural content, convenience, mood, and sensory appeal. Consumers' willingness to pay shows that they are willing to pay IDR 10,416 for "simple to make," IDR 19,410 for "ready in no time," IDR 11,549 for "contain natural ingredients," IDR 2,101 for "make them feel good when consumed," IDR 24,287 for "smell nice," and IDR 26,334 for "look good." These findings provide essential implications for SMEs, guiding product development towards fiber-rich and additive-free vegetable salads with appealing sensory attributes and easy preparation. Additionally, marketing strategies should emphasize health benefits, natural ingredients, and convenience while leveraging sensory appeal to attract a broader audience. Pricing strategies should reflect the premium consumers are willing to pay, and distribution channels should ensure accessibility. By aligning product offerings with consumer preferences and understanding their willingness to pay, SMEs can enhance their competitiveness and achieve sustainable growth in the expanding healthy food market.